Penerapan Imbal Jasa Lingkungan dalam Pelestarian Daerah Aliran Sungai di Aceh - Wardah Wardah; Lena Farsia (Kanun Jurnal Ilmu Hukum, 2013)
ABSTRACT: Payment for Environmental Service (PES) is an environmental regulatory concept that as a voluntary transaction where a well-defined environmental service is being “bought” by at least one environmental service buyer from at least one environmental service provider, if and only if the environmental service buyer secures the environmental service as a conditionality. There is increasing interest and experience in PES in both developed and developing countries. In Asia, PES concept is manifested in forest and/or water resources management policy, such as in China, Japan. In the present state of the world, PES has come to the fore in step with concerns to save the environment in a holistic manner. Now, PES has become a way or a mechanism of stakeholders to maintain and manage the environment by providing economic incentives/compensation from users to providers of environmental services. In Aceh, this mechanism is implemented for protecting river stream area, such as in Krueng Montala, Great Aceh. PES mechanisms should be supported with force of law, also synergized with policies and projects related to integrated water resources management, rural development and rural livelihoods, and land use zoning. PES mechanisms can increase the quality of nature and protect the environment also can help to provide alternative income for local people rather than they destroyed the environment. The Implementation of Payment for Environmental Services in Safeguarding The River Stream Areas in Aceh